PENERAPAN PUPUK HAYATI PADA TANAMAN PADI DI DESA TEGALMENGKEB KECAMATAN SELEMADEG TIMUR KABUPATEN TABANAN BALI - A.A.N.G. Suwastika; I.K. Suada; A.A.A.A.S. Sunari; N.W.S. Sutari (Buletin Udayana Mengabdi, 2018)
Community service is implemented in Tegalmengkeb Village of East Selemadeg District Tabanan, Bali. Thepurpose of this dedication improves the understanding and skills of farmers in the application of biofertilizeron rice crops. The method used in this activity is counselling with lectures and discussions, followed bytraining on the manufacture of local microorganisms (MOL) and the application of biofertilizer on rice crops.It is hoped that the community can apply biofertilizer technology that can improve rice crop yield andfarmer's income. The results of the training increase the understanding of farmers about biofertilizer by 30%,know about the biofertilizer and the role of biofertilizer as fertilizer of soil and plants. Increased farmers'skills in the production of local microorganisms (MOL) and can apply Egary biofertilizer to rice crops.